Eudaimonic well‐being and tumor norepinephrine in patients with epithelial ovarian cancer. Issue 19 (10th June 2015) - Davis, Lauren Z.; Slavich, George M.; Thaker, Premal H.; Goodheart, Michael J.; Bender, David P.; Dahmoush, Laila; Farley, Donna M.; Markon, Kristian E.; Penedo, Frank J.; Lubaroff, David M.; Cole, Steve W.; Sood, Anil K.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The impact of psychological well‐being on the physiologic processes involved in cancer progression remains unclear. Prior research has implicated adrenergic signaling in tumor growth and metastasis. Given that adrenergic signaling is influenced by both positive and negative factors, the authors examined how 2 different aspects of well‐being (eudaimonic and positive affect) and psychological distress were associated with tumor norepinephrine (NE) in patients with ovarian cancer. METHODS A total of 365 women with suspected ovarian cancer completed psychosocial assessments before surgery and clinical information was obtained from medical records. Study inclusion was confirmed after histological diagnosis. Tumor NE was measured in frozen tissue samples using high‐performance liquid chromatography with electrochemical detection. Confirmatory factor analysis was used to model eudaimonic well‐being, positive affect, and psychological distress, and structural equation modeling was used to examine associations between these factors and tumor NE. RESULTS Eudaimonic well‐being, positive affect, and psychological distress, modeled as distinct but correlated constructs, best fit the data (ie, compared with unitary or 2‐factor models) (root mean square error of approximation, 0.048; comparative fit index, 0.982; and standardized root‐mean‐squared residual, 0.035). Structural equation modeling analysis that included physical well‐being, stage of disease, histology, psychological treatment history, beta‐blocker use, and caffeine use as covariates was found to have good model fit (root mean square error of approximation, 0.052; comparative fit index, 0.955; and standardized root‐mean‐squared residual, 0.036) and demonstrated that eudaimonic well‐being was related to lower tumor NE (β = ‐.24 [P = .045]). In contrast, no effects were found for positive affect or psychological distress. CONCLUSIONS Eudaimonic well‐being was found to be associated with lower tumor NE, independent of positive affect and psychological distress. Because adrenergic signaling is implicated in tumor progression, increasing eudaimonic well‐being may improve both psychological and physiologic resilience in patients with ovarian cancer. Cancer 2015;121:3435–43. © 2015 American Cancer Society.